Kidney Autotransplantation in a 78-Year-Old Man with Proximal Ureteral Urothelial Carcinoma after Living Donor Nephrectomy - Wacker, Caroline; Schiffer, Mario; Richterstetter, Mario; Opgenoorth, Mirian; Apel, Hendrik (Urologia Internationalis, 2020)
Six years after living donor nephrectomy to his daughter, the 78-year-old donor presented to the emergency room with anuria for approximately 12 h. Only arterial hypertension, mildly reduced kidney function (eGFR 54 mL/min), and benign prostatic hyperplasia were known as preexisting medical conditions. In sonography, hydronephrosis III° was visible in the right single kidney. Ureterorenoscopy revealed an occlusive tumor in the right proximal ureter, which was treated via double J stent. Biopsy showed focal invasive papillary urothelial carcinoma of G2 high grade. Preoperative staging did not show any signs of lymph node or distant metastases. For therapeutic options, nephroureterectomy with consecutive need for dialysis was discussed versus partial ureteral resection with in situ ureteral reconstruction versus nephroureterectomy with partial ureteral resection and kidney autotransplantation. Eventually, laparoscopic right nephroureterectomy was performed with back-table preparation and tumor resection, followed by ipsilateral autotransplantation. The patient developed postsurgical acute kidney failure due to ischemia/reperfusion with a maximum serum Cr of 5.66 mg/dL (eGFR 10 mL/min), which quickly resolved. The papillary invasive urothelial carcinoma was graded pT1 pTis G2 high grade R0. Regular follow-ups showed no sign for cancer recurrence in computer tomography or cystoscopy; serum Cr was at 1.87 mg/dL (eGFR 53) 12 months after surgery.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Kidney autotransplantation; Living donor nephrectomy; Upper urinary tract; Urothelial carcinoma

PERICARDECTOMY AFTER PERICARDITIS CONSTRICTIVA LED TO ONSET OF TRANSPLANT KIDNEY FUNCTION AFTER 13 WEEKS OF ANURIC KIDNEY GRAFT - A CASE REPORT - Wacker, Caroline; Visconti, V.; Schiffer, Mario; Opgenoorth, M. (TRANSPLANT INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-10-29

Pericardectomy after pericarditis constrictiva led to onset of transplant kidney function after 98 days of anuric kidney graft: a case report - Wacker, Caroline; Weyand, Michael; Schiffer, Mario; Opgenoorth, Mirian (BMC Nephrology, 2020)
BACKGROUND: Constrictive pericarditis is easily overlooked and can lead to severe problems in hemodynamics and end-organ perfusion, in our patient leading to 98 days of anuria after living kidney transplantation. This was completely reversible after pericardectomy. CASE PRESENTATION: A 43-year-old female caucasian patient received a living kidney donation from her mother. She had developed end-stage renal disease 2 years prior due to nephrotic syndrome linked to graft-versus-host disease after allogenic stem-cell transplantation for aplastic anemia. The graft showed insufficient function already in the early postoperative phase. Dialysis was paused after surgery, but the patient developed hypervolemia with ascites and edema in the lower extremities. Doppler ultrasonography showed scarce perfusion, with intrarenal arterial waveforms without end-diastolic flow. The venous perfusion profiles showed pulsatile retrograde flow. There was no identifiable reason for a primary vascular perfusion problem on ultrasonography or transplant kidney angiography. Kidney transplant biopsy revealed no rejection but extensive acute tubular necrosis. Three weeks after transplantation, the patient developed an acute anuric graft failure caused by severe cardiac decompensation. Echocardiography revealed a previously unnoticed constrictive pericarditis, which could be confirmed in a cardio computed tomography scan. The constrictive pericarditis had not been apparent on previous x-rays, computed tomography scans, or echocardiographies, including those for transplantation evaluation. Conservative management of the constrictive pericarditis was not successful and the graft remained anuric. Eventually, the patient underwent pericardectomy 16 weeks after kidney transplantation. Shortly after surgery, the graft started urine production again, which significantly increased within a few days. The clearance improved and 2 weeks later, the patient was free from dialysis. CONCLUSIONS: This case illustrates that special attention should be given to the pericardium during transplant evaluation, especially for patients who previously underwent stem-cell transplantations, chemotherapy or radiation.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Case report; Constrictive pericarditis; Delayed graft function; Kidney transplant; Pericardectomy

Region-specific mechanisms of corticosteroid-mediated inotropy in rat cardiomyocytes - Wacker, Caroline; Dams, Niklas; Schauer, Alexander; Ritzer, Anne; Volk, Tilmann; Wagner, Michael (Scientific Reports, 2020)
Regional differences in ion channel activity in the heart control the sequence of repolarization and may contribute to differences in contraction. Corticosteroids such as aldosterone or corticosterone increase the L-type Ca2+ current (ICaL) in the heart via the mineralocorticoid receptor (MR). Here, we investigate the differential impact of corticosteroid-mediated increase in ICaL on action potentials (AP), ion currents, intracellular Ca2+ handling and contractility in endo- and epicardial myocytes of the rat left ventricle. Dexamethasone led to a similar increase in ICaL in endocardial and epicardial myocytes, while the K+ currents Ito and IK were unaffected. However, AP duration (APD) and AP-induced Ca2+ influx (QCa) significantly increased exclusively in epicardial myocytes, thus abrogating the normal differences between the groups. Dexamethasone increased Ca2+ transients, contractility and SERCA activity in both regions, the latter possibly due to a decrease in total phospholamban (PLB) and an increase PLBpThr17. These results suggest that corticosteroids are powerful modulators of ICaL, Ca2+ transients and contractility in both endo- and epicardial myocytes, while APD and QCa are increased in epicardial myocytes only. This indicates that increased ICaL and SERCA activity rather than QCa are the primary drivers of contractility by adrenocorticoids.
CRIS-Team Scopus Importer:2020-07-24